Neoadjuvant chemoradiation therapy for rectal cancer: current status and perspectives for the surgeon - Araújo, Sérgio Eduardo Alonso; São Julião, Guilherme Pagin; Habr-Gama, Angelita; Vailati, Bruna Borba; Perez, Rodrigo Oliva (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (May 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
Modern management of rectal cancer has become increasingly complex over the last decades. The introduction of neoadjuvant chemoradiation to the treatment strategy of locally advanced and distal rectal cancers has added numerous variables that may ultimately affect final surgical or even non-surgical management. Specific chemoradiation regimens, intervals after neoadjuvant treatment completion and tools for the assessment of tumor response may all affect final surgical decision and should be interpreted with care. The present study attempts to provide a review of commonly used neoadjuvant chemoradiation regimens, specific intervals and final surgical or non-surgical management of rectal cancer in current clinical practice.